2017
DOI: 10.1038/s41598-017-05765-4
|View full text |Cite
|
Sign up to set email alerts
|

An Amino Acid Signature Associated with Obesity Predicts 2-Year Risk of Hypertriglyceridemia in School-Age Children

Abstract: Childhood obesity is associated with a number of metabolic abnormalities leading to increased cardiovascular risk. Metabolites can be useful as early biomarkers and new targets to promote early intervention beginning in school age. Thus, we aimed to identify metabolomic profiles associated with obesity and obesity-related metabolic traits. We used data from the Obesity Research Study for Mexican children (ORSMEC) in Mexico City and included a case control (n = 1120), cross-sectional (n = 554) and a longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 32 publications
5
47
0
Order By: Relevance
“…Concentrations of serum acyl-carnitines, free carnitine, and amino acids were measured using the approach of targeted metabolomics by electrospray tandem mass spectrometry (quattro Micro API tandem MS, Waters Inc., Milford, MA, USA). Metabolite levels in serum were analyzed using the commercial kit (NeoBase Non-derivatized MS/MS Kit, Perkin Elmer, Waltham, MA, USA), as previously described [ 25 ]. Briefly, 20 µL of serum were poured onto filter paper cards (Whatman 903, Dassel, Germany) and dried at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of serum acyl-carnitines, free carnitine, and amino acids were measured using the approach of targeted metabolomics by electrospray tandem mass spectrometry (quattro Micro API tandem MS, Waters Inc., Milford, MA, USA). Metabolite levels in serum were analyzed using the commercial kit (NeoBase Non-derivatized MS/MS Kit, Perkin Elmer, Waltham, MA, USA), as previously described [ 25 ]. Briefly, 20 µL of serum were poured onto filter paper cards (Whatman 903, Dassel, Germany) and dried at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Anthropometric parameters, blood pressure and body fat mass percentage (BF%) were measured following standardized procedures, as previously described . Obesity was defined as body mass index (BMI) ≥95th percentile, whereas NW was defined as BMI between the 15th and 75th percentiles for age and gender based on Centers for Disease Control and Prevention (CDC) reference data .…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples of 5 mL were drawn after 8–12 h of fasting. Serum biochemical and amino acid analyses were carried out as previously described . Insulin sensitivity was estimated with the homeostasis model assessment for insulin resistance (HOMA‐IR).…”
Section: Methodsmentioning
confidence: 99%
“…The elevated concentrations of citrulline, proline and creatine, which are products of arginine and proline metabolism, implying the increase of amino acid utilization. Relevant metabolic articles indicated that disturbed metabolism of arginine and proline might play an important role in the obesity progression [33,34], in complete agreement with the increase in body weight and liver weight of Landes geese.…”
Section: Discussionmentioning
confidence: 54%